(untitled) (Bangladesh Agronomy Journal, 2019)
The experiment was conducted at the research field of Agronomy Division, Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur during rabi seasons of 2014-15 and 2015-16 to find out the suitable planting arrangement of squash (var. Bulam House) with maize (var. BARI Hybrid maize-9) as intercropping for higher productivity and economic return. Seven treatment combinations viz. maize normal plating (75 cm Í 25 cm), maize normal plating (75 cm Í 25 cm) (100%) + 1 row squash (Plant to Plant 80 cm) (116%), maize paired row (37.5 cm Í 150 cm Í 37.5 cm) (100%) + 1 row squash (Plant to Plant 80 cm) (50%), maize paired row (100%) + 1 row squash (Plant to Plant 100 cm) (40%), maize paired row (100%) + 2 rows squash (Plant to Plant 80 cm) (100%), maize paired row (100%) + 2 rows squash (80%) (Plant to Plant 100 cm) and sole Squash (100 cm × 80 cm) were tested. Results showed that the highest grain yield of maize (9.47 t ha-1 in 2014-15 and 9.24 t ha-1 in 2015-16) and squash yield (28.19 t ha-1 in 2014-15 and 25.02 t ha-1 in 2015-16) were recorded in sole crop, respectively. Maximum mean maize equivalent yield (19.39 t ha-1) was recorded in maize paired row (100%) + 2 row squash (Plant to Plant 80 cm) (100%) combination in both the year. The highest gross return (Tk. 2,93,850 ha-1), gross margin (Tk. 1,92,450 ha-1) and BCR (2.95) were also obtained from the same combinations. Two years’ results revealed that maize paired row + 2 rows squash (Plant to Plant 80 cm) combination could be suitable for higher productivity and economic return. Bangladesh Agron. J. 2018, 21(2): 19-24